Unambiguous Identification of β‐Tubulin as the Direct Cellular Target Responsible for the Cytotoxicity of Chalcone by Photoaffinity Labeling. (20th May 2016) - Zhou, Bo; Yu, Xingxin; Zhuang, Chunlin; Villalta, Peter; Lin, Yong; Lu, Junxuan; Xing, Chengguo
Abstract: Chalcone is a simple and potentially privileged structure in medicinal chemistry with a diverse repertoire of biological activities, among which cytotoxicity is of particular interest. The sharp structure–activity relationship (SAR) for chalcone's cytotoxicity suggests structure‐specific target interactions. Despite the numerous putative targets proposed, evidence for direct target interactions in cells is unavailable. In this study, guided by the sharp cytotoxic SAR, we developed a cytotoxic chalcone‐based photoaffinity labeling (PAL) probe, ( E )‐3‐(3‐azidophenyl)‐1‐[3, 5‐dimethoxy‐4‐(prop‐2‐yn‐1‐yloxy)phenyl]‐2‐methylprop‐2‐en‐1‐one (C95; IC50 : 0.38±0.01 μm ), along with two structurally similar non‐cytotoxic probes. These probes were used to search for the direct cellular target responsible for chalcone's cytotoxicity through intact cell‐based PAL experiments, in which β‐tubulin was identified to specifically interact with the cytotoxic probe (i.e., C95) but not the non‐cytotoxic probes. A set of phenotypical and biochemical assays further reinforced β‐tubulin as the cytotoxic target of chalcones. Peptide mass quantitation by mass spectrometric analysis revealed one peptide potentially labeled by C95, providing information on chalcone's binding site on β‐tubulin. Abstract : Best PALs : A photoaffinity labeling approach was used to search for the direct cellular target responsible for the cytotoxicity of chalcone in a whole‐cell‐based assay. β‐Tubulin was unambiguously revealed by mass spectrometric analysis to be this target. Evidence suggests that the potential binding site of chalcones on β‐tubulin is the colchicine binding site.